Iron-based amorphous micron wire catalyst and method for preparing ammonia gas through nitric acid electrochemical reduction of iron-based amorphous micron wire catalyst

By using iron-based amorphous micron wire catalyst to perform electrochemical reduction of nitric acid at lower voltages, the problem of the existing ammonia synthesis method requiring high temperature and high pressure is solved, and the effect of efficient synthesis of ammonia at normal temperature and normal pressure is achieved.

CN119530858AActive Publication Date: 2025-02-28NANJING UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411646112.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-28
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing ammonia synthesis methods require high temperature and high pressure, resulting in large energy consumption and high CO2 emissions, and low Faraday efficiency, making it difficult to efficiently synthesize ammonia at normal temperature and pressure.

Method used

Ammonia gas is prepared at a lower voltage by electrochemical reduction of nitric acid by using an iron-based amorphous microfilament catalyst. The catalyst is prepared by elements such as Fe, B, Si, Ni, Nb, P, Co, Cr, Cu, Mn by arc smelting to form a glass-covered amorphous microfilament structure.

Benefits of technology

Available ampere-level current at lower voltages, significantly reduce reaction energy consumption, improve Faraday efficiency and yield, and can efficiently synthesize ammonia at normal temperature and pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530858A_ABST
    Figure CN119530858A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-based amorphous micron wire catalyst and a method for preparing ammonia gas through nitric acid electrochemical reduction of the iron-based amorphous micron wire catalyst. When ammonia gas is prepared, the prepared iron-based amorphous micron wire catalyst is subjected to an electrochemical reduction reaction in an electrolyte solution in a three-electrode system electrolytic tank under a low voltage, and ammonia gas is produced. The prepared iron-based amorphous micron wire catalyst has the diameter of 30 microns, the specific surface area of the catalyst is effectively increased, and the current density of the catalyst is remarkably improved; the method is suitable for preparing ammonia through nitrate reduction. According to the method, commercial catalysts such as Pt and the like are replaced by metastable metal, so that the cost is low, the activity of the catalyst is remarkably improved, ampere-level current can be realized under lower voltage, the energy consumption of reaction is greatly reduced, higher Faraday efficiency and yield can be achieved at normal temperature and normal pressure, generated ammonia gas can be collected in the reaction process, and the method is suitable for industrial production. And two-in-one production and collection is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation and application of amorphous alloy electrocatalysts, and in particular to an iron-based amorphous micron-wire catalyst and a method for preparing ammonia by nitric acid electrochemical reduction thereof. Background Art

[0002] Ammonia is an important chemical raw material, widely used in chemical industry, agriculture and other fields. At present, the industry mainly relies on the Haber-Bosch method to synthesize ammonia, but the N≡N bond energy (941KJ mol-1) in the reaction substance N2 is very large, so a high temperature and high pressure environment is required. This process consumes a lot of fossil energy, which will bring about an energy crisis and cause excessive CO2 emissions. Nitrogen can be reduced to ammonia by electrocatalysis at room temperature and pressure, but it also faces the problem of high N≡N bond energy and low Faraday efficiency. It is necessary to find other methods for synthesizing ammonia, and nitrate has a lower bond energy than nitrogen, which is one of the ideal nitrogen sources for synthesizing ammonia. In addition, nitrate is one of the sources of water pollution. This technology can use nitrate in sewage as a nitrogen source, truly turning waste into treasure.

[0003] Amorphous alloys, also known as metallic glasses, use rapid cooling technology to prevent the nucleation and growth of crystals. The atoms have a disordered structure and are in a metastable state in energy. They are widely used in the field of catalysis. Iron-based amorphous micron wires can significantly improve the yield and Faraday efficiency of catalysts reducing nitrates to prepare ammonia by regulating the energy state of the material to give it more active sites. Summary of the invention

[0004] Based on the above, the present invention proposes an iron-based amorphous micron-wire catalyst and a method for preparing ammonia by electrochemical reduction with nitric acid. The current can reach the ampere level at a relatively low voltage to solve the problems of energy shortage and low yield.

[0005] The present invention proposes an iron-based amorphous micron-wire catalyst and a method for preparing ammonia by electrochemical reduction of the catalyst with nitric acid. There are three changes as follows

[0006] First, in the preparation of the catalyst, Fe, B, Si, Ni, Nb, P, Co, Cr, Cu, and Mn are prepared into amorphous alloy master alloy rods by arc melting according to atomic ratio; the master alloy is placed in a glass tube; the master alloy is softened by heating; the master alloy is pulled through an inverted tapered hole at the softened part and then drawn into a wire, and after cooling and solidification, a glass-coated amorphous micron wire is formed.

[0007] Secondly, the surface of the catalyst is coated with a layer of high borosilicate glass, which needs to be immersed in HF acid, taken out of the acid and observed under a light microscope every 30 seconds until the glass layer is completely removed, and then rinsed three times with deionized water.

[0008] In the third aspect, the use of amorphous alloy electrocatalysts is to catalyze the reduction of ammonia by nitrate. The reaction can be carried out in both H-type electrolytic cells and flow electrolytic cells, and the reaction is carried out after the anode and cathode are connected to a power source.

[0009] Specifically, the present invention provides an iron-based amorphous micron-wire catalyst, wherein the catalyst has an amorphous microstructure with a diameter of micron scale and a diameter of 20-30 μm.

[0010] In the iron-based amorphous micron-wire material structure, the iron-based amorphous metal wire serves as the core, and the outside is also wrapped with a high borosilicate glass coating layer.

[0011] It is not easy to be oxidized during the cooling process; it is particularly worth mentioning that the thickness of this coating layer is much smaller than the diameter of the metal microwire.

[0012] The preparation process of the iron-based amorphous micron-wire catalyst includes the following steps:

[0013] S1. Preparing amorphous alloy master alloy rods by arc melting;

[0014] S2. Place the master alloy in a glass tube; soften the master alloy by heating; pull the master alloy through the inverted tapered hole at the softened part to form a wire, and form an amorphous micron wire after cooling and solidification.

[0015] The iron-based amorphous microwires exist in the form of alloys, and the components are based on the metal atomic ratio:

[0016] Fe: ≥50at%, Si: 3at%~12at%, B: 5at%~15at%, P: 5at%~10at%, Nb: 0at%~3at%, Ni: 5at%~20at% and optional elements of 0at%~10at%, the optional elements are one or a combination of Co, Cr, Cu, and Mn.

[0017] The iron-based amorphous micron-wire catalyst is an alloy of Fe 63 Ni6Cr 6.5 Nb1B 13 P 6.5 Si4.

[0018] The iron-based amorphous micron-wire catalyst can produce ammonia by electrochemical reduction reaction in the electrolyte solution of the three-electrode system electrolytic cell at a low voltage. The low voltage range is -0.28 to -1.08V. The electrolyte solution can be neutral or alkaline; specifically, the nitrate concentration range is 0.1M low concentration to 2M high concentration and 1M sodium hydroxide solution.

[0019] When the iron-based amorphous micron-wire catalyst is used in an H-type electrolytic cell, the cathode region and the anode region are composed of two interconnected electrolytic cells, and the interconnected parts are separated by a proton exchange membrane;

[0020] When the iron-based amorphous micron-wire catalyst is used in a flow electrolytic cell, the cathode region and the anode region are two interconnected electrolytic cells, both of which have liquid outlets and liquid inlets at the top and bottom. The electrolyte solution flows between the electrodes, and the interconnected parts are separated by a proton exchange membrane.

[0021] The iron-based amorphous micron-wire catalyst used in the present invention has significant advantages in reducing nitrate to produce ammonia and has a wide application range compared with other catalysts.

[0022] More importantly, ampere-level current can be achieved at a relatively low voltage, greatly reducing the reaction energy consumption. These characteristics reflect the advantages of the catalyst in electron transfer, energy utilization efficiency and other aspects.

[0023] Compared with the prior art, the present invention has the following significant advantages:

[0024] 1. The present invention prepares an iron-based amorphous microwire catalyst with a diameter of 30 microns, which effectively increases the specific surface area of ​​the catalyst and significantly increases the current density of the catalyst, and is suitable for preparing ammonia by nitrate reduction; the present invention replaces commercial catalysts such as Pt with metastable metals, which is low in cost and significantly improves the activity of the catalyst, and can achieve ampere-level current at a relatively low voltage, greatly reducing the energy consumption of the reaction, so that it can have a higher Faraday efficiency and yield at room temperature and pressure, and the ammonia generated can be collected during the reaction process, realizing production and collection in one; 2. The method is simple to operate, and can significantly improve the yield and Faraday efficiency while reducing costs, and realize simultaneous production and collection. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The scanning electron microscope image of the iron-based amorphous micron-wire catalyst provided in the embodiment of the present invention shows that there is only a glass layer on the outside of the iron-based amorphous micron-wire, and the core diameter is about 30 μm.

[0026] Figure 2 The transmission electron microscope image of the iron-based amorphous micron-wire catalyst provided in the embodiment of the present invention, the high-resolution image shows that the iron-based material in the core is amorphous.

[0027] Figure 3 The energy spectrum scan of the iron-based amorphous micron-wire catalyst provided by the embodiment of the present invention shows that the seven elements in the iron-based amorphous micron-wire are evenly distributed.

[0028] Figure 4 This is a linear voltammetric scan diagram of the iron-based amorphous micron-wire catalyst provided in an embodiment of the present invention at different nitrate concentrations.

[0029] Figure 5 This is a graph showing the electrochemical stability of the iron-based amorphous micron-wire catalyst provided in an embodiment of the present invention at a current of 3A for 25 hours.

[0030] Figure 6 This is the XRD spectrum of the NH4Cl crystals obtained after acid absorption in the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0033] The present invention provides a method for preparing an electrocatalyst. The method comprises preparing a master alloy rod by arc melting according to the atomic ratio of Fe: Ni: Cr: Nb: B: P: Si = 63: 6: 6.5: 1: 13: 6.5: 4; placing the master alloy in a glass tube; softening the master alloy by heating; pulling the master alloy through an inverted cone hole at the softened part to form a glass-coated amorphous micron wire after cooling and solidification. Scanning the master alloy by an electron microscope shows the following results: Figure 1 shown.

[0034] The catalyst produced by the present invention is coated with a layer of high borosilicate glass on its surface and needs to be immersed in HF acid, taken out of the acid and observed under a light microscope every 30 seconds until the glass layer is completely removed, and then rinsed three times with deionized water.

[0035] When used in an H-type electrolytic cell, the cathode and anode regions are two electrolytic cells with a volume of 50 ml and connected at the waist, and the connected parts are separated by a proton exchange membrane; when used in a flow electrolytic cell, the cathode and anode regions are two connected special electrolytic cells (both electrolytic cells have liquid inlets and liquid outlets at the top and bottom, and the electrolyte solution flows between the electrodes), and the connected parts are separated by a proton exchange membrane. After the electrolyte flows out of the liquid outlet, it passes through the capillary, where NH3 overflows and is absorbed by the acid.

[0036] The three electrodes specifically used in the present invention are: the working electrode is a catalyst, the counter electrode is a platinum electrode, and the reference electrode is a Hg / HgO electrode. The electrolyte solution used is a 1M sodium hydroxide solution and a 0.1-2M sodium nitrate solution, and the applied voltage (vs. RHE) ranges from -0.28 to -1.08V.

[0037] Embodiment 1

[0038] In an H-type electrolytic cell, a three-electrode system was used for electrochemical reduction of nitrate, with the working electrode being a catalyst, the counter electrode being a platinum electrode, and the reference electrode being a Hg / HgO electrode. The cathode electrolyte was 50 ml of sodium nitrate (1 mol / L) and sodium hydroxide (1 mol / L) solution, and the anode electrolyte was 50 ml of sodium hydroxide (1 mol / L) solution. Constant potential electrolysis was performed at a voltage of -0.88 V for five hours, and the Faraday efficiency of nitrate reduction to ammonia was 85.9%, and the yield was 26.4 mmol / h / cm 2 .

[0039] Embodiment 2

[0040] In an H-type electrolytic cell, a three-electrode system was used for electrochemical reduction of nitrate, with the working electrode being a catalyst, the counter electrode being a platinum electrode, and the reference electrode being a Hg / HgO electrode. The cathode electrolyte was 50 ml of sodium nitrate (1 mol / L) and sodium hydroxide (1 mol / L) solution, and the anode electrolyte was 50 ml of sodium hydroxide (1 mol / L) solution. Constant potential electrolysis was performed at a voltage of -1.08 V for five hours, and the Faraday efficiency of nitrate reduction to ammonia was 80%, with a yield of 22.4 mmol / h / cm 2 .

[0041] Embodiment 3

[0042] In an H-type electrolytic cell, a three-electrode system was used for electrochemical reduction of nitrate, with the working electrode being a catalyst, the counter electrode being a platinum electrode, and the reference electrode being a Hg / HgO electrode. The cathode electrolyte was 50 ml of sodium nitrate (0.5 mol / L) and sodium hydroxide (1 mol / L) solution, and the anode electrolyte was 50 ml of sodium hydroxide (1 mol / L) solution. Constant potential electrolysis was performed at a voltage of -0.68 V for five hours, and the Faraday efficiency of nitrate reduction to ammonia was 85.24%, and the yield was 10.4 mmol / h / cm 2 .

[0043] Embodiment 4

[0044] In an H-type electrolytic cell, a three-electrode system was used for electrochemical reduction of nitrate, with the working electrode being a catalyst, the counter electrode being a platinum electrode, and the reference electrode being a Hg / HgO electrode. The cathode electrolyte was 50 ml of sodium nitrate (0.1 mol / L) and sodium hydroxide (1 mol / L) solution, and the anode electrolyte was 50 ml of sodium hydroxide (1 mol / L) solution. Constant potential electrolysis was performed at a voltage of -1.08 V for five hours, and the Faraday efficiency of nitrate reduction to ammonia was 52.15%, with a yield of 4.5 mmol / h / cm 2 .

[0045] Embodiment 5

[0046] In an H-type electrolytic cell, a three-electrode system was used for electrochemical reduction of nitrate, with the working electrode being a catalyst, the counter electrode being a platinum electrode, and the reference electrode being a Hg / HgO electrode. The cathode electrolyte was 50 ml of sodium nitrate (1 mol / L) and sodium hydroxide (1 mol / L) solution, and the anode electrolyte was 50 ml of sodium hydroxide (1 mol / L) solution. Constant potential electrolysis was performed at a voltage of -0.88 V for five hours, and the Faraday efficiency of nitrate reduction to ammonia was 82.7%, and the yield was 17.9 mmol / h / cm 2 .

[0047] Embodiment 6

[0048] In the H-type electrolytic cell, a three-electrode system was used for electrochemical reduction of nitrate, with the working electrode being a catalyst, the counter electrode being a platinum electrode, and the reference electrode being a Hg / HgO electrode. The cathode electrolyte was 50 ml of sodium nitrate (1 mol / L) and sodium hydroxide (1 mol / L) solution, and the anode electrolyte was 50 ml of sodium hydroxide (1 mol / L) solution. The electrolysis was carried out for 25 hours at a high current of 3 A / cm2, and the yield was 10.2 mmol / h / cm 2 .

[0049] Embodiment 7

[0050] In an H-type electrolytic cell, a three-electrode system was used for electrochemical reduction of nitrate, with the working electrode being a catalyst, the counter electrode being a platinum electrode, and the reference electrode being a Hg / HgO electrode. Under the interference of sulfate, the cathode electrolyte was 50 ml of sodium nitrate (1 mol / L) and sodium hydroxide (1 mol / L) solution, and the anode electrolyte was 50 ml of sodium hydroxide (1 mol / L) solution. Constant potential electrolysis was performed at a voltage of -0.68 V for five hours, and the Faraday efficiency of nitrate reduction to ammonia was 60.32%, and the yield was 10.37 mmol / h / cm 2 .

[0051] Embodiment 8

[0052] In the flow electrolytic cell, a three-electrode system is used for electrochemical reduction of nitrate, with the working electrode as a catalyst, the counter electrode as a platinum electrode, and the reference electrode as a Hg / HgO electrode. The cathode electrolyte is 50 ml of sodium nitrate (1 mol / L) and sodium hydroxide (1 mol / L) solution, and the anode electrolyte is 50 ml of sodium hydroxide (1 mol / L) solution. Constant potential electrolysis is performed at a voltage of -0.88 V for five hours. After the electrolyte flows out of the liquid outlet, it passes through the capillary, where NH3 overflows and is absorbed by the acid, achieving a two-in-one generation and collection. Figure 6 As shown, the absorbed hydrochloric acid solution is placed in an oven at 80°C for 12 hours to obtain an ammonium salt solid powder. XRD verification shows that the crystalline powder is ammonium chloride. Table 1 shows the Faraday efficiency and yield of ammonia production by the iron-based amorphous micron-wire catalyst provided in the embodiments of the present invention.

[0053] Table 1

[0054]

[0055]

[0056] The above description is only the best embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution, improvement, etc. made within the principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An iron-based amorphous micron-wire catalyst, characterized in that: The iron-based amorphous micron-wire catalyst has an amorphous microstructure with a diameter of 20-30 μm at the micron scale. In the iron-based amorphous micron-wire material structure, the iron-based amorphous metal wire serves as the core, and a high borosilicate glass coating layer is wrapped on the outside.

2. The iron-based amorphous micron-wire catalyst according to claim 1, characterized in that: The preparation process of the iron-based amorphous micron-wire catalyst includes the following steps: S1. Preparing amorphous alloy master alloy rods by arc melting; S2. Place the master alloy in a glass tube; soften the master alloy by heating; pull the master alloy through the inverted tapered hole at the softened part to form a wire, and form an amorphous micron wire after cooling and solidification.

3. The iron-based amorphous micron-wire catalyst according to claim 1 or 2, characterized in that: The iron-based amorphous microwires exist in the form of alloys, and the components are based on the metal atomic ratio: Fe: ≥50at%, Si: 3at%~12at%, B: 5at%~15at%, P: 5at%~10at%, Nb: 0at%~3at%, Ni: 5at%~20at% and optional elements of 0at%~10at%, the optional elements are one or a combination of Co, Cr, Cu, and Mn.

4. The iron-based amorphous micron-wire catalyst according to claim 3, characterized in that: The iron-based amorphous micron-wire catalyst is an alloy of Fe 63 Ni6Cr 6.5 Nb1B 13 P 6.5 Si4.

5. A method for preparing ammonia by electrochemical reduction of nitric acid using the iron-based amorphous micron-wire catalyst according to any one of claims 1 to 4, characterized in that: The iron-based amorphous micron-wire catalyst is placed in an electrolyte solution in a three-electrode system electrolytic cell at a relatively low voltage to undergo an electrochemical reduction reaction to produce ammonia.

6. The method for preparing ammonia by electrochemical reduction of nitric acid using an iron-based amorphous micron-wire catalyst according to claim 5, characterized in that: The electrolytic cell in the three-electrode system includes an H-type electrolytic cell or a flow electrolytic cell, both of which include an anode region, a cathode region, a proton exchange membrane and an electrolyte solution.

7. The method for preparing ammonia by electrochemical reduction of nitric acid using an iron-based amorphous micron-wire catalyst according to claim 6, characterized in that: When the iron-based amorphous micron-wire catalyst is used in an H-type electrolytic cell, the cathode region and the anode region are composed of two interconnected electrolytic cells, and the interconnected parts are separated by a proton exchange membrane; When the iron-based amorphous micron-wire catalyst is used in a flow electrolytic cell, the cathode region and the anode region are two interconnected electrolytic cells, both of which have liquid outlets and liquid inlets at the top and bottom. The electrolyte solution flows between the electrodes, and the interconnected parts are separated by a proton exchange membrane.

8. The method for preparing ammonia by electrochemical reduction of nitric acid using an iron-based amorphous micron-wire catalyst according to claim 5, characterized in that: The electrolyte solution may be neutral or alkaline; specifically, the nitrate concentration ranges from a low concentration of 0.1 M to a high concentration of 2 M and a 1 M sodium hydroxide solution.

9. The method for preparing ammonia by electrochemical reduction of nitric acid using an iron-based amorphous micron-wire catalyst according to claim 5, characterized in that: The low voltage range is -0.28~-1.08V.

Citation Information

Patent Citations

  • Nano-alloy electrode for electrocatalytic reduction of nitrate as well as preparation method and application of nano-alloy electrode

    CN115125567A

  • Copper-based catalyst for preparing ammonia through nitrate electroreduction and preparation method of copper-based catalyst

    CN115652338A

  • Method for preparing ammonia by reducing nitrate

    CN116479443A

  • Method for ultralow-concentration nitrate detection and efficient reduction ammonia production

    CN117443460A

  • Method for electrocatalytic synthesis of ammonia

    CN118028835A